Future Use of the Terrestric Broadcasting Spectrum below 700 MHz from 2031 Onwards - Torsten J. Gerpott (Wirtschaftsdienst)
Abstract The World Radio Conference 2023 will discuss the future dedication of ultra high frequencies in the range of 470 to 694 MHz to various users from 2031 onwards. In Germany, three stakeholder groups (1) broadcasters and programme and special events managers, (2) public mobile radio communication providers, (3) public protection, disaster relief and military defense organisations currently argue for a primary or co-primary allocation of this scarce radio spectrum for their applications. This article reviews their requests. It concludes that their cost-benefit balances are not outstanding. Consequently, an assignment of the 470 to 694 MHz frequencies after 2030 to more than these groups is likely to generate the maximum societal welfare.